Snakes and Ladders Game-Based Flipbook Media to Improve Pancasila Education Learning Outcomes in Grade III Elementary School Students - Atikah Abel Firliani; Susilo Tri Widodo (Jurnal Ilmiah Pendidikan dan Pembelajaran, 2026)
Low learning outcomes, low motivation, and limited student involvement in the learning process continue to characterize problems in Pancasila Education in elementary schools. This study aims to develop a flipbook media based on the Snakes and Ladders game, and to analyze the feasibility and effectiveness of the media in improving the learning outcomes of Pancasila Education for third-grade elementary school students. The research uses a mixed-methods approach with a research and development (R&D) focus across the ADDIE development stages. The study subjects were all 31 third-grade students in an elementary school. Data collection methods used qualitative interviews and observations, and quantitative questionnaires and pretest-posttest tests on the material of rights and obligations in Pancasila Education. Data analysis methods include normality and homogeneity tests, N-Gain calculations, and t-tests using SPSS 25. The results of the study indicate that the flipbook media based on the Snakes and Ladders game is feasible and effective for learning Pancasila Education, as evidenced by an increase in posttest scores relative to the pretest, a moderate N-Gain, and increased student motivation and active involvement. This study implies that the snakes-and-ladders flipbook media can be used more widely in elementary schools and developed to be more interactive. In conclusion, the integration of digital flipbooks with educational snakes and ladders games that combine the principles of multimedia learning and game-based learning in accordance with the characteristics of elementary school students has proven to be feasible and effective in improving learning outcomes in Pancasila Education.